SURGICAL MANAGEMENT OF PENILE PAPILLOMA LEADING TO PARAPHIMOSIS IN A DOG - MAHESH, P; KODIYATAR, MD; SUTHAR, V; PATEL, SC; PATIL, DB (The Indian Journal of Animal Reproduction, 2016)
Penile papilloma in a nondescript dog was observed as the cause of paraphimosis. Papilloma was excised surgically with excellent post-operative recovery without any adhesions between glans and prepuce.